Pengaruh Profitabilitas terhadap Manajemen Laba - Kurnia Cahya Lestari; S. Oky Wulandari (Universitas Muhammadiyah Malang, 2019)
Financial report produce information that can be used for decision made by internal such as management and employees and external such as investor, creditors and the government. However, sometimes users of financial statements are often concerned on earnings information without keep attention to the procedures used to make company profit information . This causes management to take earnings management actions. The purpose of this study was to determine the effect of profitability (Return on Asset – ROA, Return on Equity – ROE and Net Profit Margin – NPM) on earnings management in banking companies listed on Bursa Efek Indonesia (BEI). The sample used in this research is 23 banking companies listed on Bursa Efek Indonesia (BEI) within 2 years starting from 2016-2017. The research result shows that Return on Asset – ROA and Return on Equity – ROE has a significant positive effect on earning management, and Net Profit Margin – NPM does not have a significant effect on earnings management.